2015
DOI: 10.1159/000435891
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Assessment of Patients with Musical Hallucinations, Tinnitus and Hearing Loss

Abstract: Background: Although auditory hallucinations are considered a psychopathological phenomenon, musical hallucinations have been reported in individuals without psychosis but with auditory symptoms (tinnitus and/or hearing loss). Thus, a possible different cognitive functioning may be involved in musical hallucinations. The aim of the study was to characterize patients with tinnitus and musical hallucinations through a multidisciplinary assessment, allowing a better understanding of these concomitant phenomena. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Sometimes musical hallucinations have been ascribed to epilepsy when there were EEG abnormalities (not necessarily correlating with the clinical phenomenon) and/or a response to antiepileptics (i.e., pharmacological dissection); which is both questionable evidence of a relation. In another study, three out of 16 individuals with musical hallucinations (17.6%) had changes in the EEG (two with epileptiform activity in the left temporal region or in the midline/bilateral parasagittal region, and one with slow waves at the posterior temporal/left occipital regions), even though none of them exhibited symptoms of epileptic seizures [12]. A final example stems from Wengel et al [13] who noted that three out of their five patients with musical hallucinations showed temporal-lobe abnormalities on the EEG (one slow, one sharp-wave, and one alpha and theta transients).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes musical hallucinations have been ascribed to epilepsy when there were EEG abnormalities (not necessarily correlating with the clinical phenomenon) and/or a response to antiepileptics (i.e., pharmacological dissection); which is both questionable evidence of a relation. In another study, three out of 16 individuals with musical hallucinations (17.6%) had changes in the EEG (two with epileptiform activity in the left temporal region or in the midline/bilateral parasagittal region, and one with slow waves at the posterior temporal/left occipital regions), even though none of them exhibited symptoms of epileptic seizures [12]. A final example stems from Wengel et al [13] who noted that three out of their five patients with musical hallucinations showed temporal-lobe abnormalities on the EEG (one slow, one sharp-wave, and one alpha and theta transients).…”
Section: Introductionmentioning
confidence: 99%
“…According to the study in [70], Lewy body disease is the most common neurodegenerative condition, followed by Parkinson's disease and Parkinson's disease dementia. A [6] 225 General population 44 [8] 194 Audiology clinic 7 (3.6) [9] 123 Psychiatric hospital 5 (3.9) [68] 832 ENT-audiology clinics 52 [69] 16 Not specified 16 [70] 393 Mayo clinic medical records 393 [71] 24 Outpatient clinic 24 [72] 30 Psychiatric clinics handful of case reports have identified a link between MHs and structural abnormalities of the brain.…”
Section: Neurological Disordermentioning
confidence: 99%
“…These findings are consistent with those of previous studies. A recently published study examined 16 older women and determined that MHs were substantially linked to mood disorders among them [69]. Psychogenic pain, adverse childhood experiences, adaptation impairment, borderline personality disorder, attentiondeficit/hyperactivity disorder, and phase of life impairment are other psychiatric disorders linked to the onset of MHs [9,11,56].…”
Section: Psychiatric Disordermentioning
confidence: 99%
“…The study mainly reports on brain regions associated with MH, but does note that many individuals with psychiatric disorders found that the experiences were ‘mood-congruent’ (e.g., sad music when they were feeling depressed). Indeed, within psychiatric patients reporting MH, depression seems to be the most common diagnosis (69%), along with hearing loss or tinnitus ( Golden and Josephs, 2015 , Rocha et al, 2015 , Teunisse and Olde-Rikkert, 2012 ). A case series presented by Warner and Aziz (2005) of patients referred to old-age psychiatric services, though, only found a rate of hearing loss of 33% in patients with MH – perhaps surprisingly low given a mean age of 78 years.…”
Section: Introductionmentioning
confidence: 99%